Penerapan Algoritma C4.5 untuk Seleksi Penerimaan Siswa Baru pada SD Islam Terpadu Permata Bunda Demak Implementation of Decision Tree Algorithm for Selection of New Student Admission on Permata Bunda Integrated Islamic Elementary School - Linda Monizah Fitriani; Andik Setyono (Universitas Raharja, 2018)
The new admission process of selection is a basic rules for determining studying and learning in schools. This process requires precision so that the results are accurate and precise. The selection process for new students are divided into two types of screening, assessment tests and interviews. The purpose of this study is to assist schools in selecting prospective students so that they can be a decision support for new students. Thus, the need for data mining approach to generate information that can support decision-making for new admissions. The algorithm used is a C4.5 decision tree. C4.5 algorithms can support decision making new admissions through the rules generated. The testing process with RapidMiner yield 90.50% accuracy. Based on these tests, the researchers reprocess into the application form to help the school. So, do the questionnaire to the school to investigate the role of applications in the form of 10 questions by 20 teachers and an index of 81.5%. Thus, schools are satisfied with the application and can help the selection process by the school